Reasons provided for requesting a termination of pregnancy in the UK. Issue 3 (10th June 2014) - Wokoma, Tonye Telema; Jampala, Malathi; Bexhell, Helen; Guthrie, Kate A; Lindow, Stephen W
Abstract : Objective: To determine the main reasons for termination of pregnancy (TOP) requests in a UK city. Design: A survey requesting reasons for a pregnancy termination from women attending a TOP clinic. Setting: A TOP pre-assessment clinic in Hull and East Yorkshire Hospitals, UK. Population: A cohort of pregnant women requesting a TOP in the first trimester. Methods: A confidential, anonymous, self-administered questionnaire requesting demographic information about age, education, ethnicity and marital status. The questionnaire also asked for the main reasons underlying the TOP request. The main outcome measures were (1) reasons for TOP requests and (2) correlations between the reasons provided and demographic characteristics. Results: A total of 274 women participated in the study and 527 reasons were given. The most common reason was money worries (21.0%) followed closely by contraception failure (20.5%). The third most common reason was the anticipated effect on education or the woman's career (14.6%) Over half (59.5%) of the women were single and 8.8% were divorced or separated. Twenty-eight per cent of the respondents were aged 21 years and below, 36.1% were aged 22–29 years and 29.2% were over 30 years of age. Conclusions: The main reasons for TOP requests included financial constraints, contraceptive failure, completion of family, and potential interruption of education or career. These reasons differed with age groups and marital status. Focused qualitative research on reasons for a TOP will provide further knowledge and understanding that is needed to enable optimal service provision and policy planning.